2020
DOI: 10.1088/1755-1315/421/6/062043
|View full text |Cite
|
Sign up to set email alerts
|

Clover nodule bacteria as bioindicators of soils contaminated with heavy metals

Abstract: The article presents the results of a study of vital activity of nodule bacteria of Trifolium praténse, Trifolium hibridum, Trifolium alexandrinum and Trifolium incarnatum as environmentally friendly bioindicators in soil toxicity assessment. The study focused on the number of nodules and their stain with leghemoglobin. The materials were taken from the plots artificially contaminated with heavy metals (lead (Pb), arsenic (As), mercury (Hg), fluorine (F), zinc (Zn) and cobalt (Co)). The results of the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the case of Hg, several authors have demonstrated the existence of bacterial populations in the rhizosphere of various plants that have the capacity to tolerate and/or eliminate this heavy metal from the edaphic environment [ 38 ]. Other studies, such as those conducted by Nonnoi et al [ 39 ] and Bekuzarova et al [ 40 ], have isolated bacteria from root nodules of different plant species ( Medicago spp. and Trifolium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Hg, several authors have demonstrated the existence of bacterial populations in the rhizosphere of various plants that have the capacity to tolerate and/or eliminate this heavy metal from the edaphic environment [ 38 ]. Other studies, such as those conducted by Nonnoi et al [ 39 ] and Bekuzarova et al [ 40 ], have isolated bacteria from root nodules of different plant species ( Medicago spp. and Trifolium spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the rhizobium-legume symbiosis is a consequence of the evolutionary activity of leguminous plants and nodule bacteria, the result of conjugate natural selection in the process of its historical development. The high degree of heritability of symbiotic characters and the direct relationship between nitrogen-fixing ability and plant productivity testify in favor of the effectiveness of symbiotic selection [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Having knowledge in the field of increasing nitrogen fixation of legumes, scientists have proved that there are a number of biological products that can increase the leghemoglobin in nodules and their amount in accumulation of biological nitrogen on leached chernozems of the North Caucasus region [6].…”
Section: Introductionmentioning
confidence: 99%